EFEKTIFITAS KEPEMIMPINAN DALAM MENINGKATKAN KINERJA APARATUR DESA WASALABOSE KECAMATAN KULISUSU KABUPATEN BUTON UTARA - Darmanto, Darmanto; Qomariah, Erni; Bunga Batara, Suriyani (Universitas Halu Oleo, 2020)
This study aims to find out about the effectiveness of leadership in improving the performance of the apparatus in the village of Wasalabose Kulisusu District, North Buton Regency. The research used is qualitative research. Existing data collected through observation, interviews and documentation. Analysis of the data used is descriptive qualitative analysis. Research Results Show that the Leadership of the Village Head in Wasalabose is already good, as indicated by the relationship between the leaders, in this case, the Wasalabose Village Head and his subordinates and also the division of structures clear task by always giving direction in every activity carried out both in the village office or in the community and with what is done by the village head makes a strong leadership force line during the village wasalabose. Further improvement in the performance of the apparatus in the village wasalabose already has shown an increase in productivity, good service quality and responsiveness carried out by the village apparatus with the direction and instructions from their leaders namely the Head of the Village Wasalabose Kulisusu District North Regency.Â